Metode Penafsiran Ibn Qayyim dalam Tafsîr al-QurâÃ¢n al-Hakîm - fitrian Jalal, Zaglul (Mutawatir, 2012)
This article is intended as an introduction to the work of heritage interpretation Ibn Qayyim al-Jawzîyah. As an introduction course cannot be expected to complete an exposure. But from the lilte bit of description above, at least we getting conclusion that general methods are applied in interpreting. The Koran is a tahlîlî method or tajziâ. However, if viewed from term of the propensity interpretation itâs can be categorized as a al-maâthÃ»r interpretation despite as well as the interpretation of bi al-raây. As a work of interpretation, al-Qayyim interpretation may be not as famous as the work of other commentators, such as the interpretation of al-JÃ¢miâ al-Bayân, Tafsîr Ibn Kathîr, Tafsîr Jalâlayn an so on. But as a work of Muslim intellectuals seem this book need to be reviewed more thoroughly.